Digital Banking dalam Akselerasi Pemberdayaan Ekonomi Womenpreneur Indonesia : Eksplorasi Sosial-Ekonomi dan Peran LPS Berbasis PLS-SEM - Alfarizi, Muhammad; Kamila Hanum, Rastinia; Andriana Firmansyah, Almayda; Wusqo, Urwatul (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2023)
ABSTRACT Integrating technology in the digital 5.0 society, including artificial intelligence, cloud computing, and financial services, is creating a new business model: digital finance (FinTech). Indonesia's focus on economic logistics systems, FinTech development, and economic integration has positively impacted the real economy. However, digital financial innovation also brings risks, such as market uncertainty. After the pandemic, digital financial inclusion empowers women to reduce the gender gap. The history of women's economic role, such as in early Islam, highlights their success in this sector. Government measures, such as inclusive programs, show efforts to encourage women's role in the digital economy but improved financial literacy and structural support are still needed. This study aims to analyze the determinants of socio-economic conditions and the role of the Indonesian Deposit Insurance Corporation (LPS RI) in women's economic empowerment through digital banking services. This study chose a quantitative approach by conducting an online survey of 306 Indonesian womenpreneurs. The respondents' data was further analyzed using the SEM PLS analysis technique to test the proposed hypotheses. The results showed that digital banking is significant for womenpreneur empowerment in Indonesia. Financial literacy is strong, infrastructure is solid, and government support is in its favor. LPS RI protects digital banking services. recommendations including literacy campaigns, training, technology infrastructure, fiscal incentives, and government-LPS cooperation to advance womenpreneurs with financial technology.